A new species of Impatiens (Balsaminaceae) from Southwestern Thailand - Ruchisansakun, Saroj; Triboun, Pramote; Jenjittikul, Thaya (Phytotaxa, 2014)
Impatiens suksathanii Ruchis. & Triboun, a new species from a limestone area in Kanchanaburi Province in Southwestern Thailand, is described and illustrated. This endemic new species is clearly distinguished from the most similar I. namkatensis T.Shimizu by having sessile to very short petioles, linear, narrowly lanceolate to narrowly oblanceolate laminas, and pale pink flowers. Its conservation status is also assessed as Critically Endangered.